2020
DOI: 10.3390/ijms21062220
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Neurodegenerative and Cerebrovascular Disorders

Abstract: DNA methylation is an epigenetic mechanism by which methyl groups are added to DNA, playing a crucial role in gene expression regulation. The aim of the present study is to compare methylation status of healthy subjects with that of patients with Alzheimer’s, Parkinson’s or Cerebrovascular diseases. We also analyze methylation status of a transgenic Alzheimer’s disease mouse model (3xTg-AD). Our results show that both global methylation (n = 141) and hydroxymethylation (n = 131) levels are reduced in DNA sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 73 publications
(87 reference statements)
1
56
1
Order By: Relevance
“…Global DNA hypomethylation has a significant impact on the progression of various neurodegenerative diseases and can induce undesirable gene activation, leading to genomic instability [ 18 , 25 ]. To evaluate global DNA methylation, cells were treated with or without cocaine (1 µM) and piracetam (10 µM) for 24 h. We used the colorimetric method to quantify global DNA methylation (5-mC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global DNA hypomethylation has a significant impact on the progression of various neurodegenerative diseases and can induce undesirable gene activation, leading to genomic instability [ 18 , 25 ]. To evaluate global DNA methylation, cells were treated with or without cocaine (1 µM) and piracetam (10 µM) for 24 h. We used the colorimetric method to quantify global DNA methylation (5-mC).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, DNA demethylation is regulated by the ten–eleven translocation (TET) enzymes TET1-3, which help to convert 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC) [ 17 , 18 ] DNA demethylation involves the direct removal of the methyl group from 5-mC, base excision of 5-mC by DNA glycosylases, and nucleotide excision of 5-mC by endonucleases [ 19 ]. Global and site-specific changes in DNA methylation are observed in addiction [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global high levels of 5-mC and a reduction of 5-hmC were observed in the 5xFAD mouse model, which are related to cognition and paralleled with Aβ deposition (86). In the 3xTg-AD mouse model, global methylation and hydroxymethylation levels are reduced (87). In the SAMP8 mouse model, global DNA methylation levels are decreased while 5-hmC levels are upregulated (88).…”
Section: Dna Methylation/ Hydroxymethylation In Admentioning
confidence: 95%
“…Regarding DNMT3, a gene closely related to learning and memory functions [354,355], the authors observed a significant reduction of over 40% in DNMT3a expression in the brain of 3xTg-AD mice. Further evidence about the importance of DNMTs in the aging process is the fact that the hippocampus of aged mice shows a decrease in the expression of DNMT3a while its overexpression can reverse spatial memory deficits [354].…”
Section: Impact Of Dietary Factors On Dna Methylationmentioning
confidence: 98%
“…Based on the observation that the levels of 5mC and DNA methyltransferase decreased in AD patients, it has been suggested that global DNA hypomethylation is associated with AD [355]. Furthermore, the methylation level of essential substrates, such as the universal methyl donor SAM, the S-adenosylhomocystein (SAH) and folate, were also decreased in human AD brains [356].…”
Section: Impact Of Dietary Factors On Dna Methylationmentioning
confidence: 99%